Análisis de los gustos y preferencias de los propios residentes sobre la oferta gastronómica del Recinto El Tigrillo del cantón Jujan - Rivera Ruiz, Gabriela Jazmin (2021)
The objective of this research is the “Analysis of the tastes and preferences of the residents themselves regarding the gastronomic offer of the El Tigrillo area of the Jujan canton”, in this area a small variety of dishes is offered which are consumed by the residents themselves. In order to satisfy the needs of consumers, the tastes and preferences of the residents who are the ones who acquire and enjoy these dishes must be known, for the knowledge of this information a survey of sixty residents was carried out with questions about results are the dishes they prefer and you calculate they are the least consumed, their average spending of money, because they like to consume these dishes, etc. An observation sheet was also made to the positions in this enclosure where information was collected and in turn to learn a little more about these positions, observe very well their location, their hygiene, the menu they offer, the capacity they have to care for customers and finally its infrastructure was made.